Penggunaan Gadget Terhadap Kemampuan Interaksi Sosial Anak Usia Dini di TK PGRI Melati Indah - Masruroh (Education Reserach Center, 2025)
This study aims to determine the effect of gadget use on the social interaction skills of early childhood students at TK PGRI Melati Indah. The background of this research is based on the increasing use of gadgets among children without adequate supervision, which has an impact on their social development. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation involving 15 children who showed signs of gadget addiction. The results of the study indicate that uncontrolled gadget use can hinder children’s ability to interact with peers, such as being reluctant to talk, preferring solitude, and exhibiting emotional instability. The main contributing factors are the lack of parental supervision and limited social activities at home. Therefore, it is necessary to impose time limits on gadget use and encourage the active role of parents and teachers in guiding and stimulating children’s social interactions.